RECYCLING OF GREYWATER FOR AGRICULTURAL IRRIGATION: PANACEA TO HOUSEHOLD WASTE WATER MANAGEMENT - Kekere, O.; Ajibade, F. A.; Ologundudu, F. (UDS International Journal of Development, 2019)
Greywater has been identified as a widespread problem in all categories of dense settlements in Africa, due to poor or absence of waste management, thus, the quest for sustainable wastewater management. The suitability of greywater for growth and yield improvement in tomato (Solanum lycopersicum L.) and sweet pepper (Capsicum annuum L.), widely grown as field and home garden vegetables in Nigeria were tested. Seedlings grown in perforated plastic pots filled with 10 Kg top soil were irrigated till maturity with 20, 40, 60, 80 or 100% greywater while those irrigated with tap water served as the control (0%). Greywater-irrigated vegetables were taller with more number of branches and leaves than tap water-irrigated ones, but there was a general growth reduction at 100% grey water regime. Yield parameters including fruit fresh weight, fruit dry weight and number of fruits/plant were also enhanced by tap water-diluted greywater with a reduction at 100% concentration. Greywater increased mineral nutrients including N, P, K, Ca, Mg and Na in soil and fruits of test plants relative to the control. The soil and fruits of greywater-treated plants had higher concentrations of heavy metals; Cu, Zn, Pb and Cr but at a permissible level. Fruit percentage crude fibre was unaffected, protein, soluble carbohydrate and ash were generally increased in both plants while fat content was reduced by greywater at 100% regime in tomato fruits only. Reuse of greywater by dilution at 20-80% have a double-edged positive impact; it responds to the perennial quests for sustainable wastewater management and contributes to sustainable agriculture. However, there should be appropriate guidelines through research on the control and amelioration of the negative environmental impacts of repeated greywater re-use, which will further help improve overall wastewater usage and promote public acceptance of the concept. Keywords:Â Tomato, pepper, yield, fruit nutrient and proximate, domestic waste recycling, soil.